2016
DOI: 10.1007/s11605-015-2986-x
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Hypothermic Perfusion Device for Intestinal Graft Preservation to Decrease Ischemic Injury During Transportation

Abstract: This data presents proof of concept that extracorporeal intestinal perfusion is feasible. The evidence shows that the IPU can preserve the viability of human intestine, and histopathologic evaluation of perfused intestine is favorable. Our early results can eventually lead to expanding the possibilities of intestinal preservation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…Though compared to other solid organs, the long-term survival of intestinal allograft recipients remains inferior [16], in the past 10 years; there have been significant improvements in the long-term survivals for intestinal transplants. This is reflected via data from the International Intestinal Transplant Registry (ITR) through 2010, and the OPTN/Scientific Registry of Transplant Recipients (SRTR) Annual Report 2012 [76,77].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Though compared to other solid organs, the long-term survival of intestinal allograft recipients remains inferior [16], in the past 10 years; there have been significant improvements in the long-term survivals for intestinal transplants. This is reflected via data from the International Intestinal Transplant Registry (ITR) through 2010, and the OPTN/Scientific Registry of Transplant Recipients (SRTR) Annual Report 2012 [76,77].…”
Section: Resultsmentioning
confidence: 99%
“…Though organ donation after cardiac death (DCD) has increased in kidney and liver transplantation over the past decade [14], intestinal grafts from DCD donors are usually not harvested, as they are susceptible to ischemic injury [13,15], with loco-regional intestinal differences in graft vulnerability to ischemia [16]. The jejunum is very sensitive to ischemia, more than the ileum [15].…”
Section: Cadaveric Graftsmentioning
confidence: 99%
“…As the small intestine plays an important role in fluid and electrolyte homeostasis, we wished to first investigate if the previously reported side effect of diarrhea was linked to neratinib having a direct action in the small intestine. Recently, our team has developed an isolated perfusion system that allows us to look at proximal, middle, and distal small intestine while sampling the content of the lumen . The ability to have isolated intestinal segments in vitro that allow us to measure fluid secretion has been the focus of a variety of studies in our laboratory .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, our team has developed an isolated perfusion system that allows us to look at proximal, middle, and distal small intestine while sampling the content of the lumen . The ability to have isolated intestinal segments in vitro that allow us to measure fluid secretion has been the focus of a variety of studies in our laboratory . During those studies we have found that by using a luminal perfusate that contains FITC‐Inulin we can measure in real time the rate of fluid secretion or absorption in all segments of the intestine .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation